2021
DOI: 10.18019/1028-4427-2021-27-1-112-120
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and molecular entities of the etiopathogenesis of the knee osteoarthritis (literature review)

Abstract: Introduction Osteoarthritis (OA) is a heterogenic group of disorders of different etiology with similar biological, morphological and clinical manifestations and outcomes. OA is now considered a disease of the whole joint, including alterations in the articular cartilage, subchondral bone, synovial membrane, ligaments, capsule and periarticular muscles. OA of the knee as the most commonly affected joint accounts for the great medical, medical, social and economic impact. Material and methods A literature revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 0 publications
0
5
0
3
Order By: Relevance
“…Some data confirm a role NFAT5 gene plays in creating inborn immunity by activating gene expression in macrophages during TLR (Toll-like) receptor ligation [36,42,43]. We should note that immune disorders and inflammation of the syno-vial membranes (synovitis) are believed to contribute significantly to OA pathogenesis [2,44,45]. In future this may lead to "activation" of matrix metalloproteinases [46] that produce apparent proliferative and pro-inflammatory effects.…”
mentioning
confidence: 89%
“…Some data confirm a role NFAT5 gene plays in creating inborn immunity by activating gene expression in macrophages during TLR (Toll-like) receptor ligation [36,42,43]. We should note that immune disorders and inflammation of the syno-vial membranes (synovitis) are believed to contribute significantly to OA pathogenesis [2,44,45]. In future this may lead to "activation" of matrix metalloproteinases [46] that produce apparent proliferative and pro-inflammatory effects.…”
mentioning
confidence: 89%
“…These factors also cause and affect one another, creating a vicious cycle that results in the development of KOA. 10 Age is considered to be the most prominent risk factor for KOA development. 11 The aging of the body leads to degeneration of joint tissue, from subchondral bone dilatation, myelopathy, meniscus tear and compression, to cartilage defects, and a series of structural changes occur in the joint.…”
Section: Biomechanical Changementioning
confidence: 99%
“…In recent years, numerous studies have demonstrated that aging, trauma, knee dislocation, obesity, increased joint weight bearing, and decreased joint stability all play a significant role in the development of KOA. These factors also cause and affect one another, creating a vicious cycle that results in the development of KOA 10 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Имеются данные, свидетельствующие о роли NFAT5 в формировании врожденного иммунитета путем активации экспрессии генов в макрофагах при лигировании TLR (Toll-like) рецептора [36,42,43]. Стоит отметить, что в патогенезе ОА коленного сустава значимая роль отводится иммунным нарушениям и воспалению синовиальной оболочки -синовиту [2,44,45], что впоследствии может приводить к «активизации» матриксных металлопротеиназ [46], обладающих выраженными пролиферативными и провоспалительными эффектами. Известно, что TLR2 и TLR4 высокоэкспрессируются в макрофагах синовиальной жидкости и отвечают за активацию макрофагов [47].…”
unclassified